Novelties in Brazilian Lippia (Verbenaceae): two new species and two new synonyms - Cardoso, Pedro Henrique; Trovó, Marcelo; Prado, Jefferson; Neto, Luiz Menini; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2026)
Lippia diamantinensis and L. glazioviana, described in Glaziou’s catalogue (1911), are considered not validly published. They represent distinct taxonomic entities within the genus and, in accordance with the International Code of Nomenclature for algae, fungi, and plants, are here formally described as new species: Lippia neodiamantinensis and L. neoglazioviana. The former is endemic to the Diamantina Plateau, Espinhaço Range, Minas Gerais state, and the second to the Chapada dos Veadeiros, Goiás state, both from Brazil. We provide descriptions, photographs, comparisons with morphologically similar species, a distribution map, and a preliminary conservation status assessment. Additionally, Verbena goyazensis and L. possensis are proposed as synonyms of L. herbacea and L. corymbosa, respectively.